Promoting public health through nutrition labeling - a study in Brazil. Issue 1 (December 2016) - Souza, Sônia; Lima, Kenio; Alves, Maria
Abstract Background Food and nutrition education allows individuals to build knowledge and values, reframe their food practices, and develop strategies for a healthy diet. Food choices within the diet represent a determinant of individual health status. Regardless of the food quality, the consumption of calorie-dense foods does not promote better health conditions for the population and can worsen emerging health problems. The present study aimed to describe and analyze the effectiveness of educational activities related to nutrition information for enabling healthy food choices, as a tool to promote public health. Methods To describe and analyze the effectiveness of an educational intervention regarding nutrition labeling as a tool to promote healthy food choices, 702 individuals were enrolled in the present quasi-experimental study. The Wilcoxon and McNemar tests were used to compare the pre- and post-intervention data, and ap value <0.05 was considered statistically significant. Results Of the 702 participants (mean age, 26.6 years), 17.4 % were male, and 82.6 % were female. The education level was high school for 53.2 % of the participants. The mean income was R 1969.54 (about 500 USD). In the pre-test, 55.8 % of the respondents reported consulting the nutrition information provided on packaged foods. At the post-test, 72.0 % of respondents reported consulting this information (p < 0.001; Table 1). However, the change in the response regarding the purchase of packaged products was borderline significant. Conclusions The results indicate that the intervention was feasible and acceptable and improved knowledge regarding the role of nutrition labeling in promoting healthy eating. These results support the importance of an educational intervention to reinforce healthy food choices.